Falls in elderly patients with comorbidity, which were prescribed combined application of psychotropic and cardiovascular medicines - E. S. Ilina (Nervno-Myšečnye Bolezni, 2019)
The article discusses aspects of drug-induced falls in elderly comorbid patients against the background of polypragmasy and also assesses the role of drug interactions that are highly dangerous according to the risk of falling. A drug audit of the obtained pharmacotherapy database was performed in patients with comorbid pathology older than 75 years, in order to identify fall-risk-increasing drugs, ranked according to the degree of risk of falling, their significant interactions and with using the traffic light classification. The data on the analysis of the contribution of psychotropic, cardiological drugs and their combination on the risk of developing a fall in the hospital in comorbid patients of old age against polypragmasy are presented.